Properties of Fuzzy HX Ideal of a HX Ring - R. Muthuraj; N. Ramila Gandhi (International Journal of Mathematics And its Applications, 2016)
In this paper , we introduce the concept of fuzzy HX left ideal and fuzzy HX right ideal of a HX ring. Also we have discussed the properties of fuzzy HX right (left) ideal by establishing the relationship among them.